2020
DOI: 10.1177/0967391120901421
|View full text |Cite
|
Sign up to set email alerts
|

Long-term aging characteristics of co-filled nano-silica and micro-ATH in HTV silicone rubber composite insulators

Abstract: Multiple environmental stresses produce complex phenomena of aging in polymeric insulators. The main aim of this research is to investigate the improved aging characteristics of silica (SiO2)/alumina trihydrate (ATH) hybrid samples (HSs) in high-temperature vulcanized rubber. For this purpose, three HSs comprising 20% micro-ATH with 2% nano-SiO2 (S2), 4% nano-SiO2 (S4), 6% nano-SiO2 (S6) along with sample-virgin (SV) are subjected to long-term accelerated aging of 9000 h. A special aging chamber is fabricated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Khan et al studied the effects of inorganic filler ATH on the mechanical properties of sheds. The experiments showed that the particle size and added amount of ATH had little effect on the electrical properties of the sheds, but the mechanical properties were affected [ 14 , 15 , 16 ]. Wang et al [ 17 ] studied the properties of silicone rubber and fluorosilicone rubber under freezing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al studied the effects of inorganic filler ATH on the mechanical properties of sheds. The experiments showed that the particle size and added amount of ATH had little effect on the electrical properties of the sheds, but the mechanical properties were affected [ 14 , 15 , 16 ]. Wang et al [ 17 ] studied the properties of silicone rubber and fluorosilicone rubber under freezing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The aging characteristics of composite insulator shed are closely related to its operation performance, which has attracted the attention of many experts and scholars. Many studies employ static contact angle test method to analyze the aging characteristics of SIR samples [8][9][10][11] . The relationship between hardening, cracking and aging degree of composite insulator sheds has also been studied [12][13][14] .…”
mentioning
confidence: 99%
“…It appears that a further decrease in the size of the filler may increase the dielectric performance, since this offers even better penetration charge carriers through the bulk of the composite. The authors in [ 62 , 63 ] reported the results of dielectric strength of 9000 h-aged samples in a multi-stress environment of unfilled HTV-SiR and its composites filled with different fillers. Among these, HTV-SiR filled with 6 wt% nano SiO 2 + 20 wt% micro ATH gave the highest AC dielectric strength.…”
Section: Role Of Fillers On Important Properties Of Polymeric Insulatorsmentioning
confidence: 99%